The mechanics of inhaled pharmaceutical aerosols : an introduction - Finlay, Warren H. (Academic Press, 2019)
The Mechanics of Inhaled Pharmaceutical Aerosols: An Introduction, Second Edition provides a concise, but thorough exposition of fundamental concepts in the field of pharmaceutical aerosols. This revised edition will allow researchers in the field to gain a thorough understanding of the field from first principles, allowing them to understand, design, develop and improve inhaled pharmaceutical aerosol devices and therapies. Chapters consider mechanics and deposition, specifically in the respiratory tract, while others discuss the mechanics associated with the three existing types of pharmaceutical inhalation devices. This text will be very useful for academics and for courses taught at both undergraduate and graduate levels. Because of the interdisciplinary nature of this book, it will also serve a wide audience that includes engineers and scientists involved with inhaled aerosol therapies.